Systemization of accounting and taxation approaches of commission operations - Ostapiuk, Nataliia; Stashenko, Julia (Technology audit and production reserves, 2018)
The object of this research is the mechanism of commission operations and their management as a tool to optimize the use of financial resources of an enterprise. The problem is a number of issues related to the identification of a commission transaction, its documentation, the status of its participants (commission agent and committent), the methodology for calculating commission fees and determining pricing policies. As well as the order of reflection in accounting and reporting of the status and results of the implementation of these business transactions. In addition, they require solving the problem of taxation of commission operations under various tax systems and selected taxes. Theoretical and empirical research methods are used, including abstraction and specification, which provided the definition of the boundaries of commission operations and procedures for their documentation. To build a system of components of a commission operation, the methods of grouping, analogy and theoretical generalization are used to organize the accounting processes of their reflection. The use of an inductive approach and modeling contributed to the development of algorithms for optimizing the taxation of commission operations. In addition, the methods of comparison, analysis and synthesis, combined with a systematic approach, made it possible to determine the method of accounting for commission operations. As a research result, the order of accounting for commission operations of both parties to the contract specified in the work is systematized One of the ways to improve the pricing mechanism is also the abolition of the obligatory carrying out of markdown operations, as a result of which the time spent on documenting the registration and accounting process of this operation will be reduced and the interest of the committees in the intermediary services will increase. It is proposed to improve the VAT calculation in the process of carrying out commission operations. This ensures a uniform procedure for the formation of tax liabilities and tax credit of commission agents and committents, and the VAT will be paid to the budget only from commission, it allows to optimize the use of enterprise resources. Compared with the existing order, this makes it possible to optimize the contractual policy of the enterprise and the strategic planning of the enterprise’s activities.